2018
DOI: 10.1049/mnl.2017.0802
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary toxicity of exposure to nano nickel oxide

Abstract: Many articles have been reported in the literature on the relationship between exposure to nano nickel oxide (NiO) and pulmonary toxicity, but no coherent results have been achieved. This research is aimed at investigating the combined toxicity effects of pulmonary induced by nano NiO using meta-analysis. Data of cell and rat models were retrieved according to included and excluded criteria from 1994 to 2016. Twenty one articles were chosen in the meta-analysis. The standardised mean difference between the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…The IC50 values were 479.15 and 351.6 µg/mL by NRU and MTT assay, respectively (Figure 2). According to the earlier studies, The NiO-NPs induced cellular death in human neuron, liver, lung, airway epithelial, and breast cells and rat kidney epithelial cells (Abudayyak et al 2017a;Ahamed, 2011;Ahamed et al, 2013;Ahmad et al, 2013;Chang et al, 2018;Di Bucchianico et al, 2018;Horie et al, 2011;Lanone et al, 2009;Lee et al, 2015;Mohamed et al, 2018;Siddiqui et al, 2012). We could indicate that Caco-2 cells were more vulnerable than other previously studied cells to cytotoxic damage induced by NiO-NPs.…”
Section: Figurementioning
confidence: 75%
See 1 more Smart Citation
“…The IC50 values were 479.15 and 351.6 µg/mL by NRU and MTT assay, respectively (Figure 2). According to the earlier studies, The NiO-NPs induced cellular death in human neuron, liver, lung, airway epithelial, and breast cells and rat kidney epithelial cells (Abudayyak et al 2017a;Ahamed, 2011;Ahamed et al, 2013;Ahmad et al, 2013;Chang et al, 2018;Di Bucchianico et al, 2018;Horie et al, 2011;Lanone et al, 2009;Lee et al, 2015;Mohamed et al, 2018;Siddiqui et al, 2012). We could indicate that Caco-2 cells were more vulnerable than other previously studied cells to cytotoxic damage induced by NiO-NPs.…”
Section: Figurementioning
confidence: 75%
“…In positive controls (100 µM H2O2), the tail intensities were 13.3% (1.85 fold). Previously, researchers showed that the NiO-NPs could induce DNA damages in different cells (Abudayyak et al 2017a;Ahamed, 2011;Ahamed et al, 2013;Ahmad et al, 2013;Åkerlund et al, 2018;Chang et al, 2018;De Carli et al, 2018;Di Bucchianico et al, 2018;Horie et al, 2011;Lee et al, 2015;Siddiqui et al, 2012). Dumla et al (2017) reported significant DNA damages in liver, lung and kidneys of rats exposed orally.…”
Section: Figurementioning
confidence: 99%
“…A detailed analysis of these particular endpoints with considerations of various exposure routes, exposure durations, animal species, etc., is beyond the scope of this paper. However, several recently published literature reviews have evaluated many of these studies and the potential health effects of oxidic Ni NPs [ 26 , 27 , 28 ]. The acute in vivo studies evaluated in these reviews primarily focused on inflammation, histopathology, cytotoxicity, genotoxicity, oxidative stress, apoptosis, hematopoietic effects, and functional/biochemical indices.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the pulmonary clearance of inhaled NiO NPs can happen after the phagocytosis of alveolar macrophages, and the burden on the liver or blood is not considered high compared with other nanoparticles owing to the lower solubility [ 3 ]. Additionally, because NiO NPs have a higher biopersistence than other nanoparticles in the lung, they can cause chronic inflammation for 1–3 months and can persist in the lungs for up to 6 months [ 9 , 12 ]. Previous studies have reported that exposing NiO NPs to the rat lung causes acute neutrophilic inflammation through activation of NLRP3 inflammasomes and production of reactive oxygen species (ROS) [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, because NiO NPs have a higher biopersistence than other nanoparticles in the lung, they can cause chronic inflammation for 1–3 months and can persist in the lungs for up to 6 months [ 9 , 12 ]. Previous studies have reported that exposing NiO NPs to the rat lung causes acute neutrophilic inflammation through activation of NLRP3 inflammasomes and production of reactive oxygen species (ROS) [ 11 , 12 , 13 ]. NiO NPs can also reside in the lungs for a long time and induce a chronic inflammatory response [ 12 , 14 ], resulting in NiO NPs contributing to the induction of lung delayed-typed hypersensitivity (DTH) responses and pulmonary alveolar proteinosis (PAP) in rats [ 11 , 14 ].…”
Section: Introductionmentioning
confidence: 99%